Tour Operator Tourist Service - Cerón Pérez, Doris Estephanie; Morán Hernández, Karina Stéfany; Viana Cortez, Débora Beatriz (Universidad de El Salvador. Facultad de Ciencias y Humanidades, 2025)
Disponible en soporte impreso